2015
DOI: 10.1111/ped.12605
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of professional training in bereavement care: Survey of Japanese pediatricians supporting families who have lost a child

Abstract: Many pediatricians had personally provided support for the bereaved. On logistic analysis, it was considered that four factors (recognition of high risk for poor recovery, information about support, desire to study, and cooperation with professionals) were significantly associated with the professional training. There were no significant differences, however, in psychological distress, helplessness, and fatigue. Training programs related to stress management must be improved for pediatricians who feel high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Pediatricians recognize that involvement with bereaved families is left to the doctor's discretion after a child's death. This result is similar to that of a previous quantitative survey involving neonatologists and pediatric neurologists in Japan wherein doctors personally provided support to bereaved families . In a survey on bereavement care in Japanese pediatric nurses, bereavement care differed with each nurse .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Pediatricians recognize that involvement with bereaved families is left to the doctor's discretion after a child's death. This result is similar to that of a previous quantitative survey involving neonatologists and pediatric neurologists in Japan wherein doctors personally provided support to bereaved families . In a survey on bereavement care in Japanese pediatric nurses, bereavement care differed with each nurse .…”
Section: Discussionsupporting
confidence: 83%
“…This result is similar to that of a previous quantitative survey involving neonatologists and pediatric neurologists in Japan wherein doctors personally provided support to bereaved families. 9 In a survey on bereavement care in Japanese pediatric nurses, bereavement care differed with each nurse. 10 Furthermore, when a doctor coped with a child's death by himself/herself, he/she experienced mental burden.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study (Kitao et al, 2018) conducted across 64 NICUs utilized a questionnaire on coping designed by Setou and Takada (2012) and reported that nurses were significantly more likely to use coping methods if they experienced high psychological distress compared to if they were not experiencing psychological distress. Coping responses on this questionnaire included talking to colleagues, accepting the death of babies as their fate, and considering it part of their job, resting, and distraction.…”
Section: Resultsmentioning
confidence: 99%